KONSTITUSIONALISME DIGITAL DALAM SISTEM DEMOKRASI INDONESIA: ANALISIS YURIDIS TERHADAP PENERAPAN E-VOTING PADA PEMILIHAN UMUM - Wellem Hendra Balubun; Roberth Kurniawan Ruslak Hammar (PATRIOT, 2026)
Digital transformation in governance has sparked discourse on implementing electronic voting (e-voting) as an alternative voting mechanism for elections in Indonesia. However, e-voting implementation involves not only technological aspects but also raises constitutional issues regarding the protection of citizens' rights, electoral integrity, and democratic legitimacy. This study aims to analyze the status of e-voting within the perspectives of digital constitutionalism and Indonesia's democratic system, examine the implications of its implementation for the protection of citizens' constitutional rights and electoral legitimacy, and formulate an ideal regulatory model for e-voting within Indonesia's constitutional framework. The study employs a normative legal research method utilizing statutory, conceptual, and comparative approaches. The findings indicate that e-voting is not inherently at odds with the 1945 Constitution of the Republic of Indonesia, provided it upholds the electoral principles of being direct, general, free, secret, honest, and fair, while also adhering to principles of digital constitutionalism—such as transparency, accountability, cybersecurity, personal data protection, and equal accessibility. While e-voting implementation offers the potential to enhance efficiency, accuracy, and voter participation, it also carries risks regarding constitutional rights violations, the digital divide, system security vulnerabilities, and diminished public trust if not adequately regulated. Therefore, an ideal e-voting regulatory model must be established through a comprehensive legal framework, independent oversight, transparent technology audits, robust personal data protection, and a phased implementation based on infrastructure readiness and public digital literacy. In this way, e-voting can serve as an instrument to strengthen digital democracy while remaining consistent with the principles of the rule of law and popular sovereignty in Indonesia.